Three practical approaches for the synthesis of novel 4,7-dihetarylpyrazolo[1,5-a] [1,3,5] triazines (2012)
Novel 4,7-dihetarylpyrazolo[1,5-a][1,3,5]triazines were synthesized from three different approaches. The first one, involved a one-step reaction between 5-amino-3-hetaryl-1H-pyrazoles and O,S-diethyl hetaroylimidothiocarbonates or S,S-diethyl hetaroylimidodithiocarbonates under solvent-free conditions employing microwave irradiation as the energy source. In the second approach, conventional heating under reflux in DMF as solvent was used instead of the microwave irradiation; and the third one was achieved from a two-step sequence through the treatment of 5-amino-3-hetaryl-1H-pyrazoles with hetaroyl isothiocyanates and the subsequent S-alkylation and cyclization process in DMF as solvent. Some intermediates were isolated and characterized to support the regiochemistry of the studied reactions. The structures of the new compounds were unambiguously established by spectroscopic and analytical techniques.